Fossil clown beetles (Coleoptera: Histeridae): early evolution of "beetle tanks" - Simon Pražák, Jan (Univerzita Karlova, Přírodovědecká fakulta, 2023)
Clown beetles (Histeridae) represent a diverse (>4500 described species) group of beetles with worldwide distribution (except Antarctica) and with exceptional diversity of occupied habitats. Specialisation on environments such as subcortical space, dung and carrion, tunnels of wood- boring insects, caves, sand deserts, beaches, rodent burrows or ant colonies, has led to remarkable adaptations of morphology and even radical changes of entire body shape. To understand evolutionary paths of this extraordinary group of beetles, fossils are of vital importance. In this study, I examined eight undescribed species of fossil Histeridae from mid-Cretaceous Burmese and Hkamti ambers. I provide morphological descriptions and discuss possible taxonomical position of these species based on morphological characters. I further tested the phylogenetic position of all Cretaceous Histeridae genera via a topology-constrained maximum parsimony analysis based on a set of 69 characters. Among the studied species, representatives of Abraeini and Paromalini are reported for the first time from the Cretaceous. I discuss evolutionary implications based on the new as well as other Histeridae fossils. Subcortical strategy was likely common in the Cretaceous histerids, now reported in three separate lineages. It is also. Mršníci (Histeridae) představují bohatou skupinu brouků (>4500 popsaných druhů) s celosvětovým rozšířením (vyjma Antarktidy) a s výjimečně bohatou škálou obývaných habitatů. Specializace na konkrétní prostředí, jako např. podkorní štěrbiny, trus a mršiny, chodbičky podkorního hmyzu, jeskyně, písečné pouště, pláže, nory hlodavců a hnízda mravenců, vedla ke vzniku pozoruhodných morfologických adaptací či dokonce k radikálním změnám tvaru celého těla. Pro porozumnění evoluční historie této výjimečné skupiny brouků je zásadní jejich fosilní záznam. V této studii jsem zkoumal osm nepopsaných druhů fosilních mršníků ze středně křídového Barmského a Hkamtijského jantaru. Vytvořil jsem morfologické popisy a diskutuji zde ...